Coupled acoustic resonance for wave control and sensing - Lee, Taehwa; Li, Xiaopeng; Yu, Ziqi; Nomura, Tsuyoshi; Dede, Ercan M.; Iizuka, Hideo (Frontiers in Physics, 2022)
Coupled resonance enables many intriguing physical phenomena, leading to wave control and sensing. This review discusses fundamental understanding of coupled resonance by providing detailed comparison between lumped parameter-based models including coupled mode theory (CMT) and harmonic oscillator model (HOM). While reviewing recent progress in research concerning coupled resonance, emerging research areas related to coupled resonance are discussed.